Agricultural, forestry, textile and food waste used in the manufacture of biomass briquettes: a review - Espinoza-Tellez, Teófilo (2020)
In recent decades there has been a considerable global increase in urban population, industrial productivity, energy demand, waste generation, and the emission of greenhouse gases from energy conversion. The agricultural, forestry, textile and food sectors generate large amounts of waste and their environmental impact has become a major cause for concern in societies around the world. Current efforts are concerned with maximization of combustion efficiency and energy-related processes in general by making use of industrial residues and reducing particulate matter. The present review addresses the availability of different types of biomass that can be used to produce renewable energy and focuses on agricultural, forestry, urban and industrial residues. It also provides a description of the physical and calorific characteristics of the various raw materials available for the manufacture of briquettes and other fossil fuel alternatives.